The relationship between interactive use of management control system, organizational capabilities and organizational performance - Haghshenas, Zohreh (2013)
Management Control System (MCS) has attracted considerable research interests in the past decades. MCS plays an important role in providing and distributing information to support effective managerial decision-making and attainment of organizational objectives. This study focuses on the interactive use of MCS, because interactive usc of MCS facilitates exploration and identification of threats and opportunities in the environment and enables them to respond quickly to changes in the environment. Resource-based view (RBV) is an often-used framework in the study of corporate competitive strategy. This study aims to examine, from a RBV perspective, the relationship between interactive use of MCS and organizational capabilities (market responsiveness, strategic networking, process reliability and efficiency, innovativeness and learning) and their subsequent impact on organizational performance. The required data for this study were collected using a structured questionnaire, which was sent to all the companies listed in Bursa Malaysia. Seventy responses were received. Results of this study indicate that there is a positive relationship between interactive use ofMCS and organizational capabilities and overall organizational capabilities arc also directly related to organizational performance. Each type of capabilities, individually, has a positive relationship with performance, but when they are analyzed together, only process reliability and efficiency make a significant contribution to explain performance. Based on the results of the study, the overall organizational capability fully mediates the relationship between interactive use of MCS and organizational performance. It was found that not all the types of capabilities mediate the relationship between interactive usc of MCS and performance; only process reliability and efficiency partially mediates this relationship.